1999
DOI: 10.1063/1.123019
|View full text |Cite
|
Sign up to set email alerts
|

Cubic-phase GaN light-emitting diodes

Abstract: The feasibility of growing device-quality cubic GaN/GaAs(001) films by metal organic chemical vapor deposition has been demonstrated. The optical quality of the GaN films was characterized by room-temperature photoluminescence measurements, which shows a full width at half maximum of 46 meV. The structural quality of the films was investigated by transmission electron microscopy. There are submicron-size grains free from threading dislocations and stacking faults. More importantly, a cubic-phase GaN blue light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(52 citation statements)
references
References 15 publications
4
48
0
Order By: Relevance
“…3,4,5,6 It is possible, however, to grow thin epitaxial films of In x Ga 1−x N with the cubic zinc-blende (ZB) structure. 7,8,9,10,11,12,13,14 The phase stability of In x Ga 1−x N alloys has been the subject of several experimental 3,4 and theoretical studies 15,16,17,18,19,20,21,22,23,24 . For example, there have been more than ten calculations of the In x Ga 1−x N pseudo-binary phase diagram.…”
Section: 34mentioning
confidence: 99%
“…3,4,5,6 It is possible, however, to grow thin epitaxial films of In x Ga 1−x N with the cubic zinc-blende (ZB) structure. 7,8,9,10,11,12,13,14 The phase stability of In x Ga 1−x N alloys has been the subject of several experimental 3,4 and theoretical studies 15,16,17,18,19,20,21,22,23,24 . For example, there have been more than ten calculations of the In x Ga 1−x N pseudo-binary phase diagram.…”
Section: 34mentioning
confidence: 99%
“…It could be heteroepitaxied on conducting substrate instead of insulating sapphire used for h-GaN. The recent fabrication of a c-GaN LED using MOCVD [2] indicates a promising future for the blue LED. It was already demonstrated that cubic phase is preferentially grown under Ga-rich conditions [3 to 5], we have verified this tendency.…”
Section: Introductionmentioning
confidence: 98%
“…Cubic GaN (c-GaN) has enormous potential due to its easy fabrication process for blue-light emitting laser diode (LD) structure with cleaved facets [1], though the bluelight emitting LDs have been already realized by using hexagonal GaN (h-GaN) epilayers [2]. Although the growth of c-GaN epilayers on (001) GaAs or 3C-SiC has been accomplished by various methods [3 to 5], the crystalline quality of the c-GaN epilayer is not as good as the h-GaN epilayers.…”
Section: Introductionmentioning
confidence: 99%